SISTEM INFORMASI AKADEMIK BERBASIS JAVA 2 PLATFORM MICRO EDITION (J2ME) DI STMIK PPKIA PRADNYA PARAMITA MENGGUNAKAN HANDPHONE - Widayanti, Rahayu; Abdullah, Said (DINAMIKA DOTCOM, 2011)
The information system is a very important supporting factor for the development of high school, such as support in information services and data processing. STMIK PPKIA Pradnya Paramita is a campus computer that has the Academic and Student Affairs Administration serving administrative activities such as the manufacture of class schedules, exam schedules, academic calendars, handbooks, student data, the study plan card, the study results card, academic transcripts, test execution middle of the semester, and semester final exams. The Study Plan Card is a means for students to program the desired course in one semester. However, if the student can not study plan card charging directly through the system manually or through computers provided, then the student is automatically declared to stop the study while at the semester . The purpose of this research is to design information systems for mobile phones to facilitate students who can not program a course with a manual system or an existing computer system. The development of academic information system based on Java 2 Platform Micro Edition (J2ME) is expected to improve efficiency and effectiveness of academic services. Keyword : Java 2 Platform Micro Edition (J2ME), Academic information system